Analisis pola asuh anak pada keluarga miskin di lapak pemulung, Jalan Fatimah, Kelurahan Kemiri Muka, Kecamatan Beji, Depok - Nuraeni, Aisyah; Kurniawan, Aril; Ilma, Hafizha; Audy, Rheina (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Parents' behavior or treatment of children is one of the factors that influence the development of children. Findings: This relates to the way parents educate and raise children. Parenting patterns also affect the environment and have an impact on social life. This research seeks to describe and analyze the form of parenting patterns in poor families. Furthermore, it explains and analyzes the development of children in poor families in Lapak Pemulung, Jl. Fatimah, Kemiri Muka Village, Depok. Methods: The research method is descriptive through two approaches, namely field research combined with library research. Conclusion: The results obtained are an understanding that good parenting patterns produce children with development in accordance with the expectations of their parents. In addition, financial limitations are not a barrier for parents in fulfilling basic needs in the form of clothing, food and shelter.